Effect of Heat-Killed Lactobacillus paracasei KW3110 Ingestion on Ocular Disorders Caused by Visual Display Terminal (VDT) Loads: A Randomized, Double-Blind, Placebo-Controlled Parallel-Group Study. - Morita, Yuji; Jounai, Kenta; Miyake, Mika; Inaba, Masaharu; Kanauchi, Osamu (Nutrients, 2018)
Background: Visual display terminals (VDTs) emitting blue light can cause ocular disorders including eye fatigue. Some dietary constituents have been reported to be effective in improving ocular disorders while few clinical studies have been performed. We evaluated the effects of heat-killed Lactobacillus paracasei KW 3110 on improving ocular disorders and symptoms of eye fatigue among healthy human subjects with VDT loads. Methods: In vitro, the effect of L. paracasei KW3110 on blue light-induced human retinal pigment epithelial (ARPE-19) cell damage. For clinical studies, 62 healthy Japanese volunteers of 35 to 45 years of age who had experienced eye fatigue were randomized into two groups and given a placebo or L. paracasei KW3110-containing supplements for eight weeks. The primary endpoint was changes in VDT load-induced eye fatigue as determined by critical flicker frequency four and eight weeks after the start of supplementation. Results: In vitro, blue light-induced human retinal cell death was suppressed with the culture supernatants of cells treated with L. paracasei KW3110. In clinical study, the VDT load-induced reduction of critical flicker frequency tended to be milder in the L. paracasei KW3110 group when compared with the placebo group during the fourth week. Subgroup analysis classified by the degree of eye fatigue showed that the VDT load-induced reduction of critical flicker frequency was significantly better in the high-level eye fatigue subjects from the L. paracasei KW3110 group when compared with the placebo group during the fourth week (p = 0.020). Conclusions: L. paracasei KW3110 suppressed blue light-induced retinal pigment epithelial cell death. In the clinical study, ingestion of L. paracasei KW3110 had a potential to improve eye fatigue induced by VDT loads especially high levels of eye fatigue. However, further studies should be required to show more dependable clinical efficacy of L. paracasei KW3110.